Modulational Instability of the Second-order Bright Solitary Wave in Flattened Optical Fiber - (:unkn) unknown (My University, 2022)
The criterion of modulational instability of the second order bright solitary wave is studied in this article. The Principle consists initially in seeking all solitary wave solutions of the bright type which verify the nonlinear partial differential equation which governs the dynamics of propagation in flattened optical fibers. When the reference solution to be subjected to a disturbance is identified, the next step consists in establishing the condition of modulational stability/instability.
Keywords: African Research